Meditating Effect of FINTECH in to Real Estate Financial System on the Relationship Between Foreign Direct Investment and Economic Development - Sani Inusa Milala; Md Ariffin, Khadijah (Research in Management of Technology and Business, 2024)
The introduction of the integration of financial technology (FINTECH) with the real estate sector is increasing and Nigeria is actively participating in this transformation. This research aimed to investigate the mediating effect of FINTECH on the relationship between Foreign Direct Investment (FDI) and Economic Development, with a focus on the Nigerian real estate sector. Drawing upon a quantitative research design and a descriptive/exploratory strategy, the study employed structural equation modeling to analyze data collected from a sample of 375 real estate developers in Nigeria through the purposive sampling techniques. The study affirms that there is a positive impact of FDI on economic development. Capital infusion, technology transfer, and market integration associated with FDI are identified as significant contributors to sustained economic growth. The research also recognized the role of FINTECH in stimulating economic activities, enhancing financial inclusion, and fostering efficiency in the real estate sector. A noteworthy revelation of the study is there is mediating effect of FINTECH in the relationship between FDI and Economic Development. This highlights the transformative potential of technological advancements in amplifying the positive effects of foreign investment. The findings emphasize the need for policy integration, investment in technological infrastructure, capacity building, cross-sector collaboration, and continuous monitoring to harness the synergies between FDI and FINTECH for comprehensive and sustainable economic development.